New Approaches to the Analysis of the Security Environment and their Importance for Security Management - Hofreiter, Ladislav; Maris, Ladislav; Lukac, Ludek; Kister, Lukasz; Grzywna, Zbigniew (Communications - Scientific Letters of the University of Zilina, 2015)
Examination of security environment in many security papers and studies is focused primarily on analysis of external security environment of different countries. Analyzing the current security problems led us to the realization that the security environment is characterized by a systemic arrangement in which there are systems of lower and higher order. We want to demonstrate that to ensure safety of the reference object at a lower level (e.g., small social groups, individuals) it is important to evaluate the security environment of the lower order (i.e., at sub-regional, local and sub-local level). Defining and analyzing security environment at lower levels is a prerequisite for creating effective situational prevention strategies and for improving personal safety of citizens and their property.
Keywords: security environment; security situation; security management